Unlocking the potential of party research: Bringing sociology back in - Ringel, Leopold; Schank, Jan; Krichewsky, Damien; Brichzin, Jenni (Politik, 2019)
Research on political parties is a rich field, its origins dating back more than a century. Sociology played a crucial role in the foundation of party research. However, while party research has narrowed its scope and agenda, thus overlooking significant contributions from sociology, sociology has neglected the significance of political parties in the study of related social phenomena. To address this mismatch, the article explores how a sociological outlook on political parties can open up new research questions by conceptualizing political parties as embedded in societal processes, by accounting for various informal processes in party organizations, and by investigating the political profession with a comprehensive practice-based lens.